STUDI EKSPERIMENTASI PERBANDINGAN KARAKTERISTIK CAMPURAN TANAH BERPASIR DAN KAOLIN DENGAN CARA DYNAMIC DAN STATIK COMPACTION - Gawit Hidayat (INFO-TEKNIK, 2010)
One of the many factors that affect the compaction is the way of its compaction, the common ways which used in laboratory are Standard and Modified Proctor. The aim of this research are to use the comparison of characteristic value of soil mixtures of Padalarang Sandy Soil and Nagrek Kaolinite in the static and dynamic compaction and find a relationship among CBR with Static and Dynamic Cone Penetrometer.This research shows that at the same condition of dry density and optimum water content the compacted soil with static way get static force 8 ton and 11 ton to close standard and modified proctor results, and also to have the characteristic values less bigger than dynamic one about 3.75% to 46.68%. This item can be shown by permeability tests and the characteristics by california bearing ratio, static and dynamic cone penetrometer. Besides the water content, the percentage of Padalarang Sandy Soil and Nagrek Kaolinite’s mixture very affect the mechanic properties such as increasing of soil against the mixture with Nagrek Kaolinite will tend decreasing  the CBR and qc  value  and   increasing N DCP value. The trend of regresion curve resulted by static and dynamic compaction is similar. The approach equations which often used are non linear equations therefore the results are in a good enough and satisfied regresion coefficient about 0.8 to 1.Based on the result of tests also show that the soil mixtures of Padalarang Sandy Soil and Nagrek Kaolinite is not stable against soaked process where can be seen with the tedency of the characteristic value can not be measured in the soaked condition.